Understanding public trust in water managers: Findings from the Netherlands. (15th December 2021) - Voogd, Remko; de Vries, Jasper R.; Beunen, R.
Abstract: Public trust in water managers is often considered an important precondition for the effective implementation of sustainable water-management practices. Although it is well known that general public trust in government institutions is under pressure, much less is known in the literature on water governance whether such distrust also affects general and task-specific trust of the wider public in water managers. In addition, empirical studies on the determinants of such trust seem to be scarce. To fill those gaps, this study aims to measure general and task-specific public trust in water managers in the Netherlands and to assess how a selected group of potential determinants is related to general- and task-specific trust in water managers. To this end, we employ an original survey among a representative sample of the Dutch population (N = 2262). We find that trust in water managers in the Netherlands is generally high, but that it also comes with some task-specific variations. People have more trust in the flood-protection capacities of the water managers than in the capacities to successfully manage surface-water quality, nature conservation, and drought management. Using linear regression models, we subsequently find that individual-level variations in trust in water managers are best explained by one's general level of political trust. Additionally, we also show that both risk perceptions and self-evaluations of how informed people feel themselves about water management are important factors with (curvilinear) relations with trust in water managers. Overall, we conclude that water managers are under specific conditions able to build themselves well-established reputations and relatively high trust levels based on their performances. Nevertheless, trust development is far from entirely in the hands of the water managers themselves as we also conclude that trust evaluations of water managers are not immune from negative generalized political evaluations and public perceptions on water related risks. Highlights: Public trust in Dutch water managers is substantially higher than political trust Drought management and nature conservation receive less trust than flood prevention Distrust in politics in general negatively affects one's trust in water managers Stronger personal and societal risk perceptions raise the bar to trust water managers Feeling oneself better informed on water management not necessarily enhances trust